Texts and traditions religion in Shakespeare, 1592-1604 - Groves, Beatrice 1978- (Oxford Clarendon, 2007)
Explores Shakespeare's engagement with the religious culture of his time. Through readings of a number of plays - Romeo and Juliet, King John, 1 Henry IV, Henry V, and Measure for Measure, this work explains allusions to the Bible, the Church's liturgy, and to the mystery plays performed in England in Shakespeare's boyhood.
Electronic reproduction.
Keywords: Shakespeare, William -- 1564-1616 -- Religion; Catholic Church -- In literature; Bible -- In literature; Christianity and literature -- History -- 16th century. -- England; Christian drama, English -- History and criticism; Catholics -- History -- 16th century. -- England; Religion in literature